Optical waveguide coupler fabrication based on time variation ion-exchange technique - Kok, Swee Leong (2004)
Optical power transfer in a planar waveguide directional coupler is dependent on the geometry and refractive indices of the two waveguides. A method for fabricating optical directional couplers using ion-exchange Ag+/K+/Ca+ processes are presented, where the time of ion-exchange process is used to control the ratio of output power at the two output ports at a fixed temperature of 300 C. As far as the device geometry is still in single-mode regime, this method eliminates the need for high-resolution lithography for producing exact geometry of the device.